The Syntax and Prosody of Focus: the Bantu-Italian Connection - Zubizarreta, M Luisa (IBERIA: An International Journal of Theoretical Linguistics, 2010)
This paper provides an overview of the literature on the syntax and prosody of focus in some of the Bantu languages (Kimatuumbi, Chimwiini, Chichewa) and in Italian, and it argues that. despite their typological distance, they share much in common with respect to both the syntax and prosody of focus: 1) both language types have an active low Focus position (Belletti 2004, Aboh 2007) 2) the Focus position triggers the insertion of a strong prosodic boundary, which gives rise to a “ripple effect” in that phrases to the right of Foc are similarly flanked by a comparable prosodic boundary. The view outlined here argues in favor of a stronger syntax-prosody connection than is generally recognized in current approaches